Stories of Change: Rwanda: Understanding how Rwanda created an enabling environment for improvements in nutrition and the challenges that remain - Iruhiriye, Elyse; Olney, Deanna K.; Ramani, Gayathri V.; Heckert, Jessica; Niyongira, Emmanuel; Frongillo, Edward A. (International Food Policy Research Institute, 2019)
Understanding the context-specific causes of child malnutrition, including those related to political commitment and program and policy coherence, is essential for effectively reducing the prevalence of nutrition-related problems such as stunting and anemia and their subsequent negative impacts on human and national development. Between 2005 and 2015 Rwanda made substantial progress in reducing malnutrition, reducing stunting and anemia among children < 5 years of age by 14 and 15 percentage points, respectively. Despite these improvements, stunting and anemia remain important nutrition issues for young children in Rwanda with the prevalence of stunting (38%) among the highest in the world [8]. Furthermore, stunting reduction has varied across the country with some districts experiencing declines in stunting (“reduced stunting districts”), while in others stunting has either increased or stayed the same (“non-reduced stunting districts”). To facilitate greater progress in reducing child malnutrition in Rwanda, we conducted a Stories of Change Study which aimed to document the drivers of stunting and anemia reduction in Rwanda, understand what may have contributed to the variation in stunting reduction across districts, and to understand the remaining nutrition problems and the potential barriers and facilitators to future progress. The overall goal is for these results to be used by program implementers and policymakers to refine programs and policies to further reduce child malnutrition in Rwanda. This study was modeled after similar studies conducted in Bangladesh, Ethiopia, Odisha (India), Nepal, Senegal, and Zambia under the Stories of Change in Nutrition project.